Plastination: ethical and medico-legal considerations - Bin Paola; Conti Adelaide; Buccelli Claudio; Addeo Giuseppe; Capasso Emanuele; Piras Mauro (Open Medicine, 2016)
The international plastination phenomenon has proved to be immensely popular with audiences world-wide. Never before has the human body been exposed to public gaze in such an accessible manner. The exhibitions have perplexed many, included anatomists, some of whom find the display of human bodies unethical. The objective of this study is to review the attention on the use of plastination and exhibition of entire human bodies for non-educational or commercial purposes. The nature of these exhibitions and the uneasy balance between entertainment and education has caused heated debate. The possible legitimacy of the expression of one’s will as far as exhibition purposes isn’t considered sufficient for the indiscriminate use of a corpse despite the ethical necessity of respecting the wishes of individuals based on respect for the deceased. The informed consent of an individual represents only the most basic and minimal prerequisite for the use of the deceased’s body for exhibition purposes, and is absolutely not enough on its own to justify its use in entertainment exhibitions or for the commercialization of the death